2016
DOI: 10.1016/j.jtusci.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and validated spectrophotometric determination of two antifungal drugs in pharmaceutical formulations using an ion-pair complexation reaction

Abstract: Simple, rapid, cost-effective, sensitive and extractive spectrophotometric methods were developed for the determination of two antifungal drugs (i.e., sertaconazole nitrate (SER) and miconazole nitrate (MCO)) in pure and dosage forms. The methods are based on the formation of ion-pair complexes between the drugs and acid dyes (i.e., bromocresol purple (BCP), bromophenol blue (BPB) and methyl orange (MO)) in acidic buffer solutions. The formed complexes were extracted with chloroform and measured at 410, 416 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Miconazole Nitrate (MIC) an imidazole antifungal agent that is used topically and by intravenous infusion, miconazole nitrate is the nitrate salt form of miconazole, an antifungal synthetic derivative of imidazole and used in the treatment of candidal skin infections. A review of the literature showed that methods reported for the determination of (MIC) alone or in combinations were spectrophotometry [21][22][23][24][25][26][27][28], HPLC [29][30][31][32][33][34][35], HPTLC [31,[36][37][38], gas chromatography [39,40], and electrochemical methods [41]. Gentamicin (GM) is a mixture of isomeric aminoglycoside antibiotics (gentamicin C 1 , gentamicin C 1A , and gentamicin C 2 ) produced by Micromonospora purpurea or M. echinospora.…”
Section: Introductionmentioning
confidence: 99%
“…Miconazole Nitrate (MIC) an imidazole antifungal agent that is used topically and by intravenous infusion, miconazole nitrate is the nitrate salt form of miconazole, an antifungal synthetic derivative of imidazole and used in the treatment of candidal skin infections. A review of the literature showed that methods reported for the determination of (MIC) alone or in combinations were spectrophotometry [21][22][23][24][25][26][27][28], HPLC [29][30][31][32][33][34][35], HPTLC [31,[36][37][38], gas chromatography [39,40], and electrochemical methods [41]. Gentamicin (GM) is a mixture of isomeric aminoglycoside antibiotics (gentamicin C 1 , gentamicin C 1A , and gentamicin C 2 ) produced by Micromonospora purpurea or M. echinospora.…”
Section: Introductionmentioning
confidence: 99%
“…Few methods based on color reactions like condensation [20] and charge-transfer complexation [21] are found in the literature for the determination of DEC in bulk drug and dosage forms. Extractivespectrophotometry is widely used in pharmaceutical analysis [22][23][24][25][26][27][28][29][30] because of its sensitivity and selectivity; the technique also finds use in the assay of DEC in pharmaceuticals. The charge-transfer complex formed by the interaction between the chloranilic acid and DEC [31] was adopted for the assay of the drug in pure powder and in tablets.…”
Section: Introductionmentioning
confidence: 99%